Peningkatan Literasi Lingkungan pada Siswa di Sekolah Dasar Guna Membangun Generasi Cerdas Iklim - Rahmat, Hayatul Khairul; Niazi, Hakam Ali; Oktaviani, Retno Fuji; Veronika, Nina; Arif, Fadli; Syah, Nurhasan (PT Hakhara Akademia Indonesia, 2025)
Climate change and environmental degradation are pressing global challenges that need immediate attention. One crucial step in addressing these issues is to increase awareness and knowledge about the environment among the younger generation, particularly elementary school students. Environmental literacy can help students understand environmental issues, climate change, and their impacts on their lives and the future of the planet. This article proposes a community service program aimed at improving environmental literacy among elementary school students as an effort to build a climate-smart generation. The program involves an educational and practical approach, focusing on enhancing knowledge about environmental issues, developing practical skills for environmental conservation, and instilling a sense of responsibility toward nature. It is expected that this program will contribute positively to creating a more environmentally conscious, caring, and active generation that plays a role in preserving the environment and addressing climate change in the future.